MRI May Be More Valuable than Pelvic Radiographs in the Assessment of Paediatric Borderline Acetabular Dysplasia - Hans-Christen Husum; Michel Bach Hellfritzsch; Mads Henriksen; Martin Gottliebsen; Ole Rahbek (MDPI AG, 2023)
The osseous acetabular index (OAI) and cartilaginous acetabular index (CAI) is often used in diagnosing acetabular dysplasia (AD) in children. We examined the reliability of OAI and CAI in AD diagnostics and compared OAI measurements obtained from radiographs versus MRI. Four raters performed retrospective repeated measurements of the OAI and CAI on pelvic radiographs and MRI scans of 16 consecutive patients (mean age 5 years (2-8)) examined for borderline AD during a period of 2½ years. In MRI, the image selected for analysis by the raters was also registered. Spearman's correlation, scatter plots, and Bland-Altman (BA) plots were analysed for correlation between OAI on pelvic radiographs (OAIR) and MRI scans (OAIMRI), while intra- and interrater reliability was assessed for OAIR, OAIMRI, CAI, and MRI image selection using intraclass correlation coefficients (ICC). ICC values for inter- and intrarater reliability of OAIR, OAIMRI, and CAI were all above 0.65, with no significant differences observed. ICC values (CI) for individual raters' MRI image selection was 0.99 (0.998-0.999). The mean difference (95% CI) between OAIR and OAIMRI was −0.99 degrees (−1.84; −0.16), while the mean absolute difference (95% CI) between OAIR and OAIMRI was 3.68 degrees (3.17; 4.20). Absolute differences between OAIR and OAIMRI was independent of pelvic positioning or time interval between radiographs and MRI scans. OAI and CAI had high Intrarater reliability but mediocre interrater reliability. There was an absolute difference of 3.7 degrees in OAI between pelvic radiographs and MRI scans.